Desarrollo de un candidato a material de referencia para la detección y cuantificación de Escherichia coli O157 H7 por PCR (2020)
The E. coli O157: H7 is an enterohemorrhagic bacteria producing Shiga toxin. It can trigger diseases such as hemolytic uremic syndrome (HUS) and hemorrhagic colitis. It has been found associated with outbreaks of foodborne illness. Therefore, it is important to ensure their absence in the production chain of agroindustrial products through the use of sensitive, fast and specific measurement systems such as PCR. There are currently different methods to identify and quantify E. coli O157: H7 in several matrices, but there is no equivalence or comparability between the results of the measurements produced by these methods, due to the absence of traceable reference materials to the international system of units. In order to contribute to the comparability and traceability of the measures carried out by methods based on nucleic acid amplification, a candidate for reference material (MR) of genomic DNA from E. coli O157: H7 was first made in Colombia. After optimizing the culture and DNA extraction conditions of the microorganism, two batches were prepared with concentrations of 172 ± 30 copies / µL and 164864 ± 13096 copies / µL (Uα=0,95; k=2), they proved to be homogeneous and stable for 3 months. In the characterization of the MR candidate a method was used by digital PCR in droplet mode, validated to detect and quantify E. coli O157: H7 DNA in a measurement range of 8 to 8000 copies/μL with measurement uncertainty between 1.5 to 10% depending on the concentration level. The reference material produced could be used for the quality control of the measurements made by real-time PCR, allowing to establish equivalences between the measurement results obtained by the different commercial tests and guarantee traceability to the international system of units.